Przyjmowanie do klasztorów żołnierzy i małżonków w czasach Grzegorza Wielkiego na podstawie jego "Registrum epistularum" oraz norm prawa rzymskiego - Lewandowicz, Janusz (Vox Patrum, 2016)
The paper discusses the obstacles existing in both secular law and practice of the Church, in the time of St. Gregory the Great, for joining the monastery by people performing the military service or bound in marriage. Subsequently, the paper indicates higher requirements, compared with secular law, imposed by the pope on people wanting to join the monastery but bound by marriage.